Risk Management Strategies in The Financial Industry Theoretical Review and Practical Implications - Suarmanayasa, I Nengah; Pramesworo, Ignatius Septo; Masela, Anthon; Sucipto, Bambang; Launtu, Ansir (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Employee satisfaction is something that companies should pay close attention to because when the company provides job satisfaction, employees are ensured to give their best to the company. This study is a descriptive quantitative type. The research was conducted at PT. Pos Indonesia (Persero) Tapaktuan. The data used in this study are primary data. The population in this study consisted of all employees of PT. Pos Indonesia Tapaktuan, totaling 32 people. The data analysis technique used in this study is multiple linear regression assisted by SPSS software. The tests conducted in this study include validity testing, reliability testing, normality testing, multiple linear regression testing, hypothesis testing (t and f), and determinant testing. The results of the study indicate that the work environment partially influences employee satisfaction, work discipline partially influences employee satisfaction, motivation partially influences employee job satisfaction and work environment, work discipline, motivation collectively influence employee job satisfaction at PT. Pos Indonesia Tapaktuan.